Toxicity, repellency and flushing out in Triatoma infestans (Hemiptera: Reduviidae) exposed to the repellents DEET and IR3535 - Reynoso, Mercedes María Noel (2017)
DEET and IR3535 are insect repellents present worldwide in commercial products; their efficacy has been mainly evaluated in mosquitoes. This study compares the toxicological effects and the behavioral responses induced by both repellents on the blood-sucking bug Triatoma infestans Klug (Hemiptera: Reduviidae), one of the main vectors of Chagas disease. When applied topically, the Median Lethal Dose (72 h) for DEET was 220.8 μg/insect. Using IR3535, topical application of 500 μg/insect killed no nymphs. The minimum concentration that produced repellency was the same for both compounds: 1,15 μg/cm2. The effect of a mixture DEET:IR3535 1:1 was similar to that of their pure components. Flushing out was assessed in a chamber with a shelter containing groups of ten nymphs. The repellents were aerosolized on the shelter and the number of insects leaving it was recorded for 60 min. During that time, 0.006 g/m3 of the positive control tetramethrin flushed out 76.7% of the nymphs, while 1.76 g/m3 of DEET or IR3535 flushed out 30 and 0%, respectively. The concentrations required for both compounds to produce toxicity or flushing out are too high to have any practical applications. However, they showed a promising repellency. Additional research should be done to evaluate their possible use for personal protection against T. infestans bites.